PERBEDAAN LAMANYA HIDUP Trypanosoma evansi PADA BERBAGAI MEDIA - Lusita, Lulu; Kanedi, M.; Saswiyanti, Enny; Setyaningrum, Endah; Valinata, Sisca (Universitas Jambi, 2026)
The diagnosis of Surra disease has limitations that make it impossible to test Trypanosoma evansi samples directly on all samples. This is due to limitations in time and medical and paramedical personnel in field diagnosis, thus requiring research on T. evansi live media solutions. The purpose of this study was to determine the lifespan of T. evansi in various media solutions and which media solution was most effective. This study was experimental in nature, using a Completely Randomized Design (CRD) and three replicates. Data analysis was performed using the LDS test, followed by an Analysis of Variance (ANOVA) test to find significant differences in the lifespan of T. evansi in various media solutions; Phosphate Buffer Saline Glucose (PBSG), Dulbeccos Modified Eagle Medium (DMEM) 1X + GlutaMAXTM, NaCl infusion (sodium chloride 0.9%), coconut water. The results of the statistical test at room temperature showed significant differences, with the Phosphate Buffer Saline Glucose (PBSG) solution sample being the best media solution for the survival of T. evansi parasites.